Interfacial electron transfer dynamics of two newly synthesized catecholate bound ruII polypyridyl-based sensitizers on TiO2 nanoparticle surface - a femtosecond pump probe spectroscopic study - Banerjee, Tanmay; Rawalekar, Sachin; Das, Amitava; Ghosh, Hirendra Nath (Europian Journal of Inorganic Chemistry, 2011)
Two new catecholate-bound RuII–polypyridine based sensitizers, (2,2′-bipyridine){ethyl 3-(4-hydroxyphenyl)-2-[(4′-methyl-2,2′-bipyridinyl-4-carbonyl)amino]propionate}{4-[2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl]benzene-1,2-diol)}ruthenium(II) hexafluorophosphate (5) and [(2,2′-bipyridine)-(4-2,2′-bipyridinyl-4-yl-phenol)-(4-{2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl}benzene-1,2-diol)]ruthenium(II) hexafluorophosphate (6) with secondary electron-donating groups (tyrosine and phenol, respectively) were synthesized and characterized. Steady-state optical absorption and emission studies confirm strong coupling between the sensitizers and TiO2 nanoparticles. Femtosecond visible transient absorption spectroscopy has been employed to study interfacial electron transfer (IET) dynamics in the dye–nanoparticle systems to explore the influence of the secondary electron-donating groups on IET dynamics. Electron injection into the conduction band of nanoparticulate TiO2 has been confirmed by detection of the conduction band electrons in TiO2 ([e–]TiO2CB) and radical cation of the adsorbed dye (D·+) in real time monitored by transient absorption spectroscopy. A single exponential and pulse-width limited (< 100 fs) electron injection has been observed. Back electron transfer (BET) dynamics have been studied by monitoring the decay kinetics of the injected electron in the conduction band of TiO2 and by the recovery of the ground state bleach. BET dynamics in dye–TiO2 systems for complexes 5 and 6 have been compared with those of [bis(2,2′-bpy)-(4-{2-(4′-methyl-2,2′-bipyridinyl-4-yl)vinyl}benzene-1,2-diol)]ruthenium(II) hexafluorophosphate (7), which does not have a secondary electron-donating group.